(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to identify the role of performance evaluation standards in improving the quality of administrative staff performance from the perspective of primary school principals in the city of Jeddah. To achieve this objective, the descriptive survey method was used, and a questionnaire was utilized as the tool for data collection from the study population, which consisted of (225) principals. The study reached the following results: the role of evaluation standards in improving the quality of administrative staff performance in Jeddah’s primary schools was generally rated (high) from the principals’ point of view, with a general arithmetic mean of (2.53 out of 4.00), which falls within the third category of the four-point scale, indicating the degree of agreement (agree) in the study tool. It was also found that the role of social responsibility in improving job performance ranked first, with an agreement mean of (2.61 out of 4.00), followed by the role of teamwork with a mean of (2.52 out of 4.00), and in third place came the role of initiative with a mean of (2.51 out of 4.00). In the fourth and last place came the role of flexibility to change with a mean of (2.47 out of 4.00). As for the challenges facing principals in applying performance evaluation standards, they had a medium effect overall from their perspective; the mean of their agreement on the statements regarding the challenges faced by school principals in applying performance evaluation standards was (2.47 out of 4.00). The study also showed no statistically significant differences in the responses of the study sample towards evaluation standards for improving the quality of administrative staff performance attributed to the variables of educational qualification or years of experience. In light of the study, the researchers recommend the following: adopting training programs to prepare principals, encouraging principals to exchange information, experiences, and knowledge, raising employees’ awareness of the importance of volunteering to accomplish tasks, and encouraging employees to overcome problems facing the work team.